2016
DOI: 10.1111/avj.12419
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker lead perforation of the right ventricle associated with Moraxella phenylpyruvica infection in a dog

Abstract: Bacteraemia associated with M. phenylpyruvica has never been reported in the dog, but sporadic cases are reported in humans. Infection could have resulted from either pre-existing myocarditis or opportunistic infection and bacteraemia post pacemaker implantation. Evaluation of the pacemaker function at regular intervals would allow early detection of poor pacemaker-to-myocardium contact, which would prompt further investigation of pacemaker lead abnormalities such as perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…(1) presented a case of a patient in whom problems with sensing caused by lead dislodgement and right ventricular perforation were detected accidently during administration of anaesthesia seven weeks after the implantation of a passively-fixed electrode (1). Regular control of pacemaker function allows for early detection of lead malposition and for implementation of appropriate preventive measures to avoid further dislodgement (6).…”
Section: Discussionmentioning
confidence: 99%
“…(1) presented a case of a patient in whom problems with sensing caused by lead dislodgement and right ventricular perforation were detected accidently during administration of anaesthesia seven weeks after the implantation of a passively-fixed electrode (1). Regular control of pacemaker function allows for early detection of lead malposition and for implementation of appropriate preventive measures to avoid further dislodgement (6).…”
Section: Discussionmentioning
confidence: 99%
“…. 331–364 Most were case series or single case reports (LOE 5), and 1240 dogs were described, of which 60 had suspected or confirmed thrombosis (5%). Two studies were experimental (LOE 3) but of poor quality 336,361 .…”
Section: Peco Question: Transvenous Pacemaker (Dogs)mentioning
confidence: 99%
“…334,337,339,346 Eighteen studies (1 LOE 3 good, 17 LOE 5 good-fair) were judged to be neutral to the PECO question based on long-term follow-up of dogs after pacemaker implantation without reports of thrombotic complications. 332,333,336,340,342,343,[347][348][349][350][351][352][353][354]356,359,363,364 An experimental (LOE 3) study described 74 dogs with implanted pacemakers (≤180 days). A variety of complications were reported, but thrombosis did not occur.…”
Section: Evidence Summarymentioning
confidence: 99%
“…An interesting case report involving a 13‐year‐old Border Collie sparks interesting hypotheses about modes of infection in patients with pacemakers . The dog was presented with acute‐onset syncope, severe lethargy, fever and bradycardia 10 months following transvenous pacemaker implantation.…”
Section: Small Animalsmentioning
confidence: 99%
“…An interesting case report involving a 13-year-old Border Collie sparks interesting hypotheses about modes of infection in patients with pacemakers. 3 The dog was presented with acuteonset syncope, severe lethargy, fever and bradycardia 10 months following transvenous pacemaker implantation. On fluoroscopy it was found that the pacemaker tip had migrated through the apex of the right ventricle; echocardiography also demonstrated acoustic shadowing of the pacemaker lead through the right ventricle with no evidence of pericardial effusion.…”
Section: Small Animalsmentioning
confidence: 99%